Damages Observed in Turkey Due to the Kahramanmaras Earthquakes of February 6, 2023 - Tapia-Hernandez, E.; Genes, M. C.; Guerrero-Bobadilla, H. (Taylor & Francis Ltd, 2025)
On February 6, 2023, an Mw 7.8 earthquake occurred at an epicenter near Nurda & gbreve;& imath;, Turkey. The earthquake impacted 11 provinces in Turkey and Syria, resulting in significant casualties due to the total or partial collapse of many buildings. Approximately nine hours later, an Mw 7.5 induced second earthquake occurred with an epicenter near Ekin & ouml;z & uuml;. In this paper, observed damages in structural and non-structural elements identified in some post-earthquake inspections are shown and discussed in detail. The study aims at spreading the acquired knowledge and underlining relevant aspects that might improve the performance of buildings under future seismic demands.
Keywords: Turkey; field inspection; collapse mechanism; structural damage; soft-story; infill wall failure